2011
DOI: 10.1002/ange.201004245
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Nanostructures from Positively Charged Polycyclic Aromatic Hydrocarbons

Abstract: Amphiphile PQP14‐Komplexe bilden durch den Einsatz von Alkylsulfonaten oder Disulfonaten als Anionen auf kontrollierte Art und Weise zweidimensionale (2D) Nanostrukturen (siehe Bild). Die Morphologien dieser 2D‐Nanostrukturen beeinflussen die Ionenleitfähigkeit einer Mischung der PQP14‐Komplexe mit Lithiumsalzen nachhaltig. Die gebildeten planaren Aggregate weisen eine um zwei Größenordnungen höhere Leitfähigkeit auf als die faltigen Aggregate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 52 publications
(10 reference statements)
2
5
0
Order By: Relevance
“…As a consequence, the calculated XRD d spacings of the (100) reflection value are 2.04, 2.94, and 3.87 nm, respectively, on the basis of Bragg’s law. These results suggest that the compounds with longer alkyl chains have a larger interlayer spacing in the aggregates 6a…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…As a consequence, the calculated XRD d spacings of the (100) reflection value are 2.04, 2.94, and 3.87 nm, respectively, on the basis of Bragg’s law. These results suggest that the compounds with longer alkyl chains have a larger interlayer spacing in the aggregates 6a…”
Section: Resultsmentioning
confidence: 83%
“…Aggregate morphology was investigated by scanning electron microscopy (SEM). The declined solubility of formed aggregates can lead to the formation of a suspension, which can help preserving the integrity of the nanostructures, protecting them from deformation, as they are being transferred to a solid substrate 6a. We conducted the assembly of 1 – 4 from a binary solvent system in an optimized 2:3 ratio of dichloromethane/methanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[9][10][11] The selfassembled 1D nanoobjects from planar aromatics are excellent candidate for electronic and optoelectronic devices owing to the charge-transporting and energy-migrating pathway provided by the p-p interactions between the piled planar aromatics. 3, [12][13][14][15][16] Besides p-p interactions, by appropriate functionalization, various noncovalent intermolecular forces, such as hydrogenbonding, amphiphilic, and charge-transfer interactions, have been utilized as secondary forces to tailor the molecular arrangement of the polycyclic aromatics. [17][18][19][20][21] In comparing with other 1D nanostructures such as nanoribbons and fibrils, examples of p-conjugated systems that assemble into high aspect nanotubes are relatively uncommon, since strict conditions are required.…”
Section: Introductionmentioning
confidence: 99%
“…4 Aida and co‐workers have shown that an amphiphilic variant of the molecular analog to graphite; hexabenzocorenene forms nanotubes in organic solution 3c. Müllen and co‐workers demonstrated that tuning the size and structure of the counterion of the cationic discotic molecule offers new opportunities to control aggregate structures3e, 5 forming, for example, stable planar aggregates. The supramolecular aggregates mentioned above were formed in either THF or 50 to 100 % methanol solutions.…”
mentioning
confidence: 99%